(3GdLRA ajg ef GdahGFO GdefJbGI GdZQGFH GdMSGf Yf GdTjhM Gdchajjfs - (3GdfQSj, CHh GdZfGFe, eMeO Hf Ydj Hf ejehf, J (B510 (3g`s
(3ChdgG (B:s
(3HSe Gddg (B... (3CNHQfG GdTjN (B.. (3CHh GdbGSe YHO Gddg Hf GdMSjf Hf YHO Gddg Hf QhGMI GdCfUGQj GdMehj bQGAI Ydjg hCfG CSeY HMdH bGd CNHQfG GdTjN GdMGaX CHh WGgQ CMeO Hf eMeO Hf CMeO Hf eMeO Hf EHQGgje GdSdaj (B...s
(3BNQgG (B:s
.. (3CfTOfG eMeO Hf Ydj Hf YHO GdQMef GdYdhj ; CQi Gdedhc HOhf GdOjf bO bfYhG hdG CQGge QVhG aj GdYjT HGdOhf (B***(3aGSJZf HGdOjf Yf OfjG Gdedhc ceG GSJZfG Gdedhc HOfjGge Yf GdOjf (B. (3BNQ GdLRAs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B6\278s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
(3Qbej ZjQ edhfs
Keywords: (3GdMOjK hGdeUWdMs